Hypericin Suppresses SARS-CoV-2 Replication and Synergizes with Antivirals via Dual Targeting of RdRp and 3CLpro - Helena da Silva Souza; Jéssica Santa Cruz Carvalho Martins; Thiagos das Chagas Sousa; Saiqa Sardar; Natalia Fintelman-Rodrigues; Lina Silva-Trujillo; Thiago Moreno Lopes e Souza; Marilda Mendonça Siqueira; Jorge Hernandes Fernandes; Aline da Rocha Matos (Microorganisms)
The continuous emergence of SARS-CoV-2 variants underscores the need for novel antiviral candidates. Hypericin (HY), a compound derived from Hypericum perforatum, exhibited potent in vitro activity against SARS-CoV-2 in Vero E6 cells, with low cytotoxicity (CC50 > 200 nM). HY showed no significant activity against Influenza A (H1N1) or dengue virus serotype 2, supporting its selective action. Antiviral effects were most evident when HY was administered post-infection, in a concentration-dependent manner, while cellular pretreatment or viral pre-incubation produced limited effects. Notably, HY also displayed virucidal activity, significantly reducing viral titers at 4 °C, 22 °C, and 37 °C. Combination treatments with remdesivir or nirmatrelvir enhanced antiviral efficacy by 50–70% relative to monotherapy, depending on compound concentration. Molecular simulations revealed stable interactions with conserved residues in RdRp and 3CLpro, suggesting a low risk of resistance. Together, these findings highlight the potential of HY as a selective antiviral and virucidal agent against SARS-CoV-2, particularly in combination regimens.